Evaluating the In Vitro Activity of Depsidones from Usnea subfloridana Stirton as Key Enzymes Involved in Inflammation and Gout - Thanh-Trung Nguyen; Srilakshmi Nallapaty; G S N Koteswara Rao; Sree Teja Koneru; Satya Sowbhagya Priya Annam; Vinay Bharadwaj Tatipamula (Tabriz University of Medical Sciences, 2021)
Background: Traditionally, Usnea genus has significant uses in the treatment of swelling and tumors in Africa and Asia. The aim of the present study was to investigate the chemical constituents present in the acetone extract (AE) of Usnea subfloridana Stirton and also to evaluate their anti-inflammatory and anti-gout effects. Methods: Isolation and characterization of secondary metabolites from AE were evaluated by chromatography and spectral studies. Anti-inflammatory activities were assessed through cyclooxygenase (COX1 and COX2) and 5-lipooxygenase (5-LOX) enzyme inhibition assays, while anti-gout effects were evaluated by xanthine oxidase (XO) inhibition assay. Results: The existence of five known depsidones, identified as galbinic acid (1), conprotocetraricacid (2), constictic acid (3), salazinic acid (4), and lobaric acid (5), were exposed by chemical investigation of AE and confirmed by spectral data. Using in vitro enzyme inhibition assays, it was noticed that all the isolates showed dose-dependent activity against all the tested enzymes. Mainly, compounds 2 and 5 showed better inhibition efficiency on COX2 enzyme with the IC50of 7.17±1.07 and 7.01±0.94 nM, respectively, than the reference drug indomethacin (7.3±0.65nM). Furthermore, all isolates exhibited potent inhibition effects on the XO enzyme. Conclusion: The results indicated that U. subfloridana can be a favorable natural source for thetreatment of inflammation and gout. Compounds 2 and 5 were responsible for these biologicalactions by regulating pro-inflammatory enzymes, namely COXs, 5-LOX, and XO.